2015
DOI: 10.1007/s13277-015-3914-0
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the prognostic value of tumor markers and cytokines as SCCAg, CYFRA 21.1, IL-6, VEGF and sTNF receptors in patients with squamous cell cervical cancer, particularly with early stage of the disease

Abstract: The aim of this study is to determine the prognostic value of tumor markers, as squamous cell carcinoma antigen (SCCAg) and cytokeratin-19 fragment (CYFRA 21.1) and interleukin 6 (IL-6), vascular endothelial growth factor (VEGF), soluble tumor necrosis factor receptor I (sTNF RI), and sTNF RII in patients with squamous cell carcinoma of the cervix. The subjects of analysis were 138 patients with stage I–IVA according to the International Federation of Gynecology and Obstetrics (FIGO) classification. The collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Some studies reported probability of outcome occurrence or median survival, leaving 44 studies for final pooling of association effects. Among these 44 studies, 31 [14,15,19,21,23, and 26 [14,22,23,28,30,36,37,39,[42][43][44][45][46][47][48][50][51][52][53][54][55][56][57][58][59][60] assessed association effects of pretreatment serum SCC-Ag on recurrence and death outcomes respectively, while 8 [9,19,[23][24][25]31,61,62] and 4 [23,24,60,62] assessed posttreatment SCC-Ag effects on these corresponding outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies reported probability of outcome occurrence or median survival, leaving 44 studies for final pooling of association effects. Among these 44 studies, 31 [14,15,19,21,23, and 26 [14,22,23,28,30,36,37,39,[42][43][44][45][46][47][48][50][51][52][53][54][55][56][57][58][59][60] assessed association effects of pretreatment serum SCC-Ag on recurrence and death outcomes respectively, while 8 [9,19,[23][24][25]31,61,62] and 4 [23,24,60,62] assessed posttreatment SCC-Ag effects on these corresponding outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Among 31 studies assessing association between pretreatment serum SCC-Ag and recurrence, 14 [15,21,[28][29][30][32][33][34][35]38,43,45,48,49] and 18 [14,19,28,[37][38][39][40][41][42][43][44][45][46][47][48]50,51,53] assessed high versus low SCC-Ag providing frequency data and HR, respectively; whereas 8 [19,21,29,30,32,36,48,52] studies compared mean SCC-Ag between groups.…”
Section: High Versus Low Scc-agmentioning
confidence: 99%
See 2 more Smart Citations
“…6 However, these methods are traumatic and costly. 7,[9][10][11] Thus, studying the peripheral blood circulating microRNAs (miRNAs) has important clinical value for the treatment, diagnosis and prognostic value of cervical cancer. 8 Biomarkers such as tissue polypeptide antigen (TPA), squamous cell carcinoma antigen (SCC-Ag), vascular endothelial growth factor (VEGF), and carcinoembryonic antigen (CEA) are confined to specific types of the cervical cancer but lack sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%